The genus Meleonoma Meyrick (Lepidoptera: Autostichidae) from Thailand - Wang, Shuxia; Tao, Zhulin (Zootaxa, 2020)
Two new species of the genus Meleonoma Meyrick, 1914 from Thailand are described: M. segregacantha sp. nov. and M. fornicalis sp. nov. A checklist and a key to all the seven species from Thailand are given. Images of adults and genitalia of the new species are provided.